CLIENT SATISFACTION AND DECISION MAKING AMONGST FEMALES VISITING FAMILY PLANNING CLINICS IN HYDERABAD, PAKISTAN - Memon, Arbia; Hamid, Saima; Kumar, Ramesh (Journal of Ayub Medical College Abbottabad, 2017)
Background: Family Planning is the basic right of the human being. It involves decision regarding the number of children and desired space between children by the couple themselves. Quality services involving multiple dimensions build the confidence of the clients and lack of quality is one of the constraints behind incomplete coverage of family planning. Objectives of the current study were to determine the client satisfaction, decision-making process and various influences on clients in adopting family planning methods. Methods: This cross-sectional study was conducted at Family Planning Centre of Liaquat University Hospital, Hyderabad in 2016. Quality of the family planning services and satisfaction with the services were assessed through responses obtained from women selected purposively and visiting family planning centre through exit interviews with structured pretested and reliable questionnaire after taking the written consent. Results: Access to Family Planning Centre was not an issue in 92% cases but only 31% respondents were appropriately greeted, 77% faced blank expression and 13% received sufficient privacy. Health problems and socioeconomic conditions were inquired by 41% and18% providers respectively, while motivating force for service use was mother in law in most 35% cases. Health workers were successful in clarifying misinformation (86%) and explaining side effects (71%) but only 21% respondents were satisfied with services. Respondents are influenced by family and health care providers while making decision and type of influence was considered positive by 83% respondents. Conclusion: Training and monitoring system be strengthened at family planning centres to improve quality of services while important influencing relations be focused for family planning education to improve utilization of services. Keywords: Family planning services; contraception; Pregnancy; decision-making